From conventional accounting to Islamic accounting does it need a slight or an extensive overhaul - Rizal Setya Yaya (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2001)
Most of Muslim scholars that involve in the development of accounting based Islamic teachings agree on the need of an Islamic accounting for the development of accounting and Auditing institution. This has been exercised in the development of accounting and Auditing Standard for Islamic Financial Institution (AAOIFI. However to what extent the overhaul should be made to obtain an Islamic accounting is subject to debate among those scholars . The debate ranges from the need of slight changes on conventional accounting to the extensive changes on conventional accounting. This paper analyzes both opinions based on their ability to achieve the Islamic socioeconomic objective.